Machining-induced surface integrity of Inconel 718 alloy fabricated by powder bed fusion additive manufacturing under various laser processing parameters - (:unkn) unknown (Taylor and Francis Ltd., 2022)
Parameters used in laser powder bed fusion (LPBF) process are key factors that influence the surface integrity and thus mechanical properties of Inconel 718 components fabricated by additive manufacturing (AM) technique. For this reason, various parameters with different settings through trial and error approach have used by AM community to fabricate Inconel 718 components. These AM fabricated components generally required post treatment or processing including finish machining, to enhance their surface properties. This study presents a systematic investigation on the effect of volumetric energy density, and various LPBF processing parameters including laser power, layer thickness, and scanning speed on the as-printed specimens and the surface integrity aspects, namely surface quality, porosity, and microhardness. Furthermore, using machining operations specifically finish milling on these specimens under constant machining parameters, the effect of as-printed conditions on the machinability responses including burr formation, cutting forces are evaluated accordingly. Moreover, the interrelationship between LPBF processing parameters-machining-surface and subsurface aspects are also examined. This study reveals that LPBF additive manufacturing parameters have remarkable influence on the printed Inconel 718 specimens. Results also showed that parameters including laser power, scanning speed and layer thickness also have an effect on both the machinability and final surface and subsurface properties of the AM fabricated Inconel 718 specimens. It should be also noted that there is a notable relationship between volumetric energy density and the machinability of the AM printed Inconel 718. © 2021 Taylor & Francis Group, LLC.
Keywords: finish machining; Inconel 718; porosity; Powder bed additive manufacturing; surface integrity; volumetric energy density